KUALITAS FISIK DAGING DADA DAN PAHA BROILER YANG DIRENDAM DALAM LARUTAN DAUN SALAM (Syzygium polyanthum) - Dian Septinova; Madi Hartono; Purnama Edy Santosa; Siti Hartika Sari (JURNAL ILMIAH PETERNAKAN TERPADU, 2018)
The objectives of the study were (1) to know there was or no interaction between soaking time in bay leaf and type of carcass to the physical quality of broiler meat; (2) To know the duration of optimum immersion for the physical quality of the muscles of the breast and thighs. This research was arranged using Completely Randomized Design (RAL) with factorial pattern. The first factor is the length of meat immersion in bay leaf solution, namely: P0: control; P1 (20 minutes); P2 (40 minutes); P3 (60 minutes). While the second factor is a piece of carcass, namely: K1 (thigh) and K2 (chest). Each treatment was repeated 3 times. The research variables were pH of meat, WHC, and cooking loss. The data obtained were proceed to variance analyze and further tested by BNT  Test for length of  immersion and Tukey test for carcass type at 5% level of significant. The results showed that there was no interaction (P>0,05) between soaking time and carcass cut. The duration of immersion had no significant (P>0,05) effect on pH, WHC, and cooking loss. Carcasses cut of thight and breast have a significant effect (P<0,05) on pH and cooking loss, but are not significant (P>0,05) for WHC. The pH value of the thigh meat is significantly (P<0,5) higher than the breast, but the cooking loss is lower. Keywords :  Bay Leaf, Breast, Thight, Broiler, Physical Quality